Health Status of Senior Citizens of Dalit and Non-Dalit Community (The Mega Journal, 2024)
The study investigates the distinctive characteristics of senior citizens, with a focus on Dalit and Non-Dalit communities in Malarani Rural Municipality, Nepal. Covering demographics, socio-economic factors, and health statuses, the research involves 430 individuals aged 60 and above. Historical marginalization of Dalit’s raises the possibility of unique challenges for them in aging. The utilizing chi-square tests, identifies significant associations between various factors, such as age, literacy, income, and health, among Dalit and Non-Dalit individuals. The chi square analysis underscores the impact of age, literacy, education, religion, employment, income, retirement, and blood pressure on senior citizens in Dalit and Non Dalit communities. Notably, possession of assets, land, home, and other variables showed no significant differences between the age (60-64 to 85+) groups. The study suggests that intergenerational programs and active aging initiatives can enhance the well-being of older adults and foster inclusive communities. Understanding these dynamics is crucial for addressing the distinct needs of senior citizens, particularly those from historically marginalized communities.